Said Nursi’s Psycho-spiritual Therapy for Psychological Reactions of Patients with Physical Illnesses - Nabil, MR Ahmad; MFM, Tahir; NS, Thomas; H, Gülerce (IIUM Medical Journal Malaysia, 2019)
Depression and anxiety are relatively common psychological reactions among those with chronic physical illnesses.1 It has been associated with low quality of life and impairment of daily functions.1 Cognitive behavioral therapy has been shown to be effective in helping patients to deal with maladaptive beliefs about their illnesses that predispose and perpetuate the psychological reactions.2 An event e.g. illness, may be interpreted differently by different individuals from a cognitive point of view.2 A person who attaches an unrealistic extravagant meaning to it, will result in an excessive emotional reaction. The cognitive content of a depressed patient centers on significant loss e.g. health, while an anxious patient harbors thoughts of imminent danger e.g. fear of loss.2